Moving Online: A Pilot Clinical Trial of the Changing Talk Online Communication Education for Nursing Home Staff. (21st December 2020) - Williams, Kristine N; Coleman, Carissa K; Perkhounkova, Yelena; Beachy, Tim; Hein, Maria; Shaw, Clarissa A; Berkley, Amy
Abstract: Background and Objectives: Staff–resident communication is a critical part of nursing home (NH) care. Reducing elderspeak and increasing person-centered communication has been shown to reduce behavioral symptoms experienced by persons living with dementia. An online version of a successful classroom-based communication-training program that reduced staff elderspeak and resident behavioral symptoms was evaluated. The objective of this study was to establish feasibility and determine the preliminary effects of the online program in preparation for a national pragmatic clinical trial. Research Design and Methods: Seven NHs were randomized to immediate intervention or wait-list control conditions. The NHs were provided with the web-based training program that staff individually accessed. Primary outcomes were knowledge scores and communication ratings of a video-recorded interaction, using pre- to posttraining comparisons. Results: Knowledge increased from a mean pretest score of 61.9% ( SD = 20.0) to a mean posttest score of 84.6% ( SD = 13.5) for the combined group. Knowledge significantly improved between Time 1 and Time 2 for the immediate intervention participants ( p < .001), but not for the wait-list control participants ( p = .091), and this difference was statistically significant ( p < .001). Ability to recognize ineffective, inappropriate, nonperson-centered, and elderspeak communication improved after training ( p < .001). The magnitude of improvement in communication recognition was comparable to that of the original classroom format. Discussion and Implications: The adapted communication intervention was feasible and improved knowledge and communication. Online instruction can improve access to quality education and is an effective means to improve dementia care by overcoming barriers to in-person training. Clinical Trials Registration Number: NCT03849937